The Influence of Human Resource Management and Organizational Culture on The Quality of Service in The Purwasari Sector of Police (Dinasti International Journal of Management Science, 2026)
The purpose of this study was compiled to answer the formulation of the problems that have been determined, namely To analyze the influence of Human Resource Management on Service Quality, To analyze the influence of Human Resource Management on Service Quality and To analyze the simultaneous influence of Human Resource Management and Organizational Culture on Service Quality at Purwasari Police. The t-value for variable X1 is 4.308, the t-table value for N = 70 is 1.994. So 4.308 > 1.994, the influence of Human Resource Management (X1) has an effect on Service Quality (Y), the t-value for variable X2 is 4.308, the t-value for N = 70 is 1.994. So 4.308 > 1.994, it is concluded that Organizational Culture (X2) has an effect on Service Quality (Y) ANOVA test of 54.931 which is greater than the f table value for N = 70 of 2.74 or 54.931 > 2.81 with a significant level of 0.000 because 0.000 < 0.05, then the Influence of Human Resource Management (X1) and Organizational Culture variables (X2) together have an effect on the Service Quality variable (Y).